PERLINDUNGAN HUKUM TERHADAP NASABAH PERBANKAN SYARIAH DALAM KASUS PEMBIAYAAN BERMASALAH - Danti, Annisa; Surya Hamdani; Mutiara Nauli (Universitas Haji Sumatera Utara, 2024)
Sharia banking has developed rapidly in Indonesia as a financial alternative that is in line with Islamic principles, offering products and services that are free from usury, gharar and maisir. However, legal protection for customers in cases of problematic financing is a significant challenge. This research aims to evaluate existing legal protection mechanisms and identify the challenges faced by customers when facing problems in sharia banking financing. Through qualitative and quantitative approaches, this research collects data from case studies, interviews with legal practitioners and customers, as well as surveys about customer experiences in dispute resolution. The research results show that although sharia banking regulations in Indonesia, such as Law Number 21 of 2008 and the DSN-MUI fatwa, provide a legal framework for sharia banking, there are shortcomings in their practical application, especially in handling problematic financing cases. The main obstacles identified include legal uncertainty in regulations, limited dispute resolution mechanisms, and low customer satisfaction with existing legal protection. Dispute resolution mechanisms, especially through sharia arbitration institutions, are often considered less efficient and not fully transparent, which can reduce customer trust. This research recommends several steps for improvement, including revising regulations to provide clearer guidance, increasing transparency and efficiency in sharia arbitration institutions, as well as implementing educational programs for customers to understand their rights and the dispute resolution process. By implementing these recommendations, it is hoped that legal protection for sharia banking customers can be improved, providing certainty and justice in dealing with problematic financing cases.